Effect of Total Mixed Ration Based Complete Pellet Feed on the Performances of Stall Fed Native Sheep - Ahmed, S; Rakib, MRH; Hemayet, MA (SAARC Journal of Agriculture, 2021)
A complete pellet feed was developed using 40 % roughage (Rice straw) and 60 % concentrate (Rice polish 50 %, Maize crush 16 %, Soybean meal 20 %, Molasses 10 %, Salt 2 %, DCP 1 %, Vitaminmineral premix 0.5 %, Pellet binder 0.5 %) for commercial sheep production under stall feeding system. To know the effect of complete pellet feed on animal performances, both on-station and on-farm trials were conducted in growing sheep. The results of the experiment demonstrated that in the traditional system of rearing; only 22.42 g daily weight gain was observed. While, feeding of complete pellet feed achieved 84.98 g, and 100.67 g daily weight gain at on-farm and on-station condition respectively suggesting that pelleting enhanced the efficiency of utilization of feed. However, no differences were observed for the feed cost per kg weight gain, feed conversion ratio (FCR) and benefit-cost ratio (BCR) among the pellet feeding group and other group. But results suggest that complete pellet feed would be more economical for commercial sheep production under the stall-fed condition and farmers would be more benefited using complete pellet feed compared to conventional grass or urea molasses straw (UMS) and concentrate based feeding system. No disease or clinical symptoms were observed in the animals during the experimental period, suggesting that pellet feeds are well accepted by the sheep and results in better growth rate. SAARC J. Agri., 18(2): 157-166 (2020)